دراسة مقارنة لأنشطة ترويحية ريلضية في بعض المتغيرات الفسيولوجية لكبار السن الممارسين والغير ممارسين في لعبة كرة القدم - سي موسى, عمر (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
Abstract : Study title: Comparative study of some functional variables between recreational sports practitioners and non practitioners . The aim of the study was to learn about the impact of recreational sports activity on BMI and heartbeat in the 45-55 age group, using a sample research sample: members of the 45-55 age group and Cunat about 20 individuals, who were divided into two groups such as : Group I: 10 recreational sports activity practitioners (football) . Group II: 10 do not engage in any sporting activity. In our research, we relied on the use of the descriptive method, using the BMI measurement test and the heartbeat comfort test as a research tool, and the most important results of sports recreational activities were a positive impact on BMI and heartbeat at the 45-55 age group. There are statistically significant differences in BMI between the 45-55 age group for practitioners and non-practitioners of recreational sports activity. There are statistically significant differences in the heartbeat in a case between the age group of 45-55 and practitioners and non-practitioners of recreational sports activity . The following statistical tools have been used : ➢ Arithmetic average . ➢ Standard deviation . ➢ Natural distribution test . ➢ Alpha Cronbach persistence coefficient . ➢ Test T Student .
MEPS-2024-56
Keywords: الأنشطة الترويحية الريلضية - المتغيرات الفسيولوجية - كبار السن- كرة القدم